The role of socialization network to understand the adoption of demand‐reduction behaviors: The red siskin's breeders community case study - Ada Sánchez‐Mercado; Lisandro Moran; Arlene Cardozo‐Urdaneta; Lisbeth Bethelmy (Conservation Science and Practice)
Abstract The unsustainable and illegal trade of passerine birds, such as the threatened red siskin (Spinus cucullatus), is deeply embedded in social, economic, and cultural systems. Understanding these complexities is essential for designing effective behavioral interventions to reduce unsustainable wildlife demand. We used social network analysis, decision‐making models, and interview data from 204 breeders involved in red siskins captive breeding across Venezuela (a source and demand country), Brazil, Spain, and Portugal (demand countries) to explore how socialization networks, shape their decisions to adopt sustainable bird sourcing practices. Adoption intentions were partially explained by psychosocial variables such as attitudes and social norms towards breeders' collaboration. Incorporating social network metrics, such as information flow, significantly improved model explanatory power. Actors classified as adults in formation were the most active advice‐seekers (high outdegree) and the lowest adoption intention. Brazil and Venezuela had a clear relationship between membership proportion and network coordination metrics, but not Portugal and Spain. We discuss how to use the insights of the breeder’ psychosocial and their roles within the network, to inform tailored behavior change strategies. These results emphasize the importance of integrating insights into breeders' behaviors and roles within networks to inform tailored behavior change strategies.